2005
DOI: 10.1073/pnas.0408749102
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of an antiviral compound from the internal pocket of human rhinovirus 14 capsid

Abstract: WIN antiviral compounds bind human rhinovirus, as well as enterovirus and parechovirus, in an internal cavity located within the viral protein capsid. Access to the buried pocket necessitates deviation from the average viral protein structure identified by crystallography. We investigated the dissociation of WIN 52084 from the pocket in human rhinovirus 14 by using an adiabatic, biased molecular dynamics simulation method. Multiple dissociation trajectories are used to characterize the pathway. WIN 52084 exits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
(51 reference statements)
0
20
0
Order By: Relevance
“…A better understanding of the insertion and passage of the lipophilic Q/QH2 through the portal could be gained through molecular dynamics analysis, as studied in the passage of ubiquinone through a defect in the ring of light-harvesting (LHI) bacteriochlorophyll molecules surrounding the photosynthetic reaction center (234), and the insertion of a drug molecule into a virus capsid protein (235), which has a formal resemblance to quinol insertion into the p-side entry portal to the [2Fe-2S] cluster. The combination of kinetic and steric constraints of portal entry-extrusion of quinol/quinone in the most frequent description of the Q cycle, described symbolically in Fig.…”
Section: The Problem Of the P-side Portalmentioning
confidence: 99%
“…A better understanding of the insertion and passage of the lipophilic Q/QH2 through the portal could be gained through molecular dynamics analysis, as studied in the passage of ubiquinone through a defect in the ring of light-harvesting (LHI) bacteriochlorophyll molecules surrounding the photosynthetic reaction center (234), and the insertion of a drug molecule into a virus capsid protein (235), which has a formal resemblance to quinol insertion into the p-side entry portal to the [2Fe-2S] cluster. The combination of kinetic and steric constraints of portal entry-extrusion of quinol/quinone in the most frequent description of the Q cycle, described symbolically in Fig.…”
Section: The Problem Of the P-side Portalmentioning
confidence: 99%
“…The method was introduced by Pettitt over 20 years ago, but has seen limited usage. The major proponents of the method have been May and Brooks[49, 5457] and Post[5861]. …”
Section: All-atom Modelingmentioning
confidence: 99%
“…Thus, all five structural elements that the neutralizing VHHs bind in common (possibly except for the distal GH loop of VP1) lie in direct contact either with the pocket factor itself or with hydrophobic residues that line the pocket. Computational dynamics simulations by Li et al (32) on a complex between rhinovirus 14 and the capsid-binding drug WIN52084 showed that the pocket occupant can snake its way out of the pore (the outer, hydrophilic open end of the pocket) without significantly perturbing the native virus structure, except in three specific, localized areas of VP1. These areas included the C beta strand and the EF loop (both of which are common VHH contact areas) and the middle of the G beta strand.…”
Section: Figmentioning
confidence: 99%